Beat osteoporosis — nourish and exercise skeletons (BONES): a group randomized controlled trial in children. - Economos, Christina D..; Hennessy, Erin.; Chui, Kenneth.; Dwyer, Johanna.; Marcotte, Lori.; Must, Aviva.; Naumova, Elena N..; Goldberg, Jeanne. (Tufts University. Tisch Library., 2020)
Keywords: Bone, Randomized controlled trial, Osteoporosis, Weight loading physical activity, Calcium, Child, Health behavior.; Springer Open.